LESSON STUDY GERBANG PENINGKATAN MUTU PENDIDIKAN DAN PROFESIONALISME GURU DI DAERAH PESISIR PULAU TARAKAN - Kadek Dewi Wahyuni Andari; Agustinus Toding Bua; Aidil Adhani (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2020)
Quality education is a significant challenge in the aspects of life. It because by globalization and rapid technological developments. The phenomenon that occurs on learning in primary schools, especially coastal areas requires qualified human resources. Qualified human resources are expected to utilize and manage the natural resources available. Learning in primary school, for example, in the town of Tarakan already well underway. Equipped with adequate learning infrastructure, schools were comfortable situation, and teachers who are competent enough in their field. However, something else is happening in the coastal areas in particular Tarakan Island Binalatung area where people mostly depend fishermen, seaweed farmers, even less so their children participate in fishing and leave lessons to aid her parents earn a living. Through lesson study conducted in the first grade at SDN 016 Tarakan, the model teacher and observer gain valuable experience as assisted in observing students with problems to be more attention and students are smart be facilitated learn better and this learning process be a reflection of the teachers that teach the team becomes more useful as well as for the evaluation of teachers in teaching.